MEMPERTIMBANGKAN AMANDEMEN KONSTITUSI (KAJIAN CALON PRESIDEN PERSEORANGAN DARI ASPEK KEDAULATAN RAKYAT DAN KONSTITUSIONALISME) - rudy, rudy (Lampung University, 2014)
Peoples expectations of the political party the less, as seen in the decline of voter participation and cynicism on the performance of the elite in the executive and legislative branches. Of his own political party, does not appear seriousness introspection headed clear modern party program and the recruitment of cadres. In the midst of apathy towards political parties at this time, and the approach of the national public needs to elect a president who can fix the state of the nation and state, discourse of individual presidential candidates should be encouraged through mechanisms that reflect the state of law based on democratic constitution. Through the constitutional process, the results will reflect the development of constitutionalism systematic, holistic, and focused and not constitutionalism sporadic development and pragmatic.Â Keywords: Amandement, Sovereignty of the People, ConstitutionalismÂ